Development of cempaka SMART school for the elderly as an improvement of elderly welfare in Bengkulu - Nabila, Yani Deliza; Nopianti, Heni; Himawati, Ika Pasca (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
The research examines the development of the Cempaka SMART Elderly School in improving the welfare of the elderly in Bengkulu City focusing on the seven dimensions of resilient elderly. The research used descriptive qualitative methods. Informants were selected using a purposive sampling technique. The research was analyzed using Talcott Parsons' Functional Structural theory. The results showed that Sekolah Lansia is a learning program designed for elderly people 60 years and over, namely elderly people who have potential in the family and community. This program aims to improve knowledge and behavior, covering the dimensions of elderly welfare in Bengkulu City. These seven dimensions are spiritual, physical, emotional, intellectual, social, vocational, and environmental. The development of Sekolah Lansia includes program and curriculum development, facilities and access, and learning methods. Research highlights the importance of spiritual well-being, social support, and participation in recreational activities for the elderly, as these aspects have an influence on the overall happiness and quality of life of the elderly. In addition, encouraging independence, life satisfaction and engagement in meaningful activities are key strategies to improve well-being and happiness for older adults.